2017
DOI: 10.1016/j.schres.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Association of sFlt-1 and worsening psychopathology in relatives at high risk for psychosis: A longitudinal study

Abstract: Background Angiogenic dysfunction and abnormalities in psychopathology and brain structure have been reported in schizophrenia, but their relationships are mostly unknown. We recently demonstrated that sFlt-1, anti-angiogenic factor, was significantly elevated in patients at familial high-risk for psychosis (FHR). We hypothesized that elevated sFlt-1 correlates with baseline and longitudinal changes in psychopathology, cognition, and brain structure. Methods Plasma sFlt-1 in FHR (n=35) and HC (n=39) was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…However, our findings align with animal studies, which have shown that VEGFA , VEGF receptor 1 (VEGFR1/Flt-1), and VEGF receptor 2 (VEGFR2/KDR) signaling affect working memory primarily by modulating neuroplasticity at the hippocampus or through peripheral neurotrophic effects 1 6 , 33 . Our findings are further supported by human studies, which have demonstrated that the effects of psychotic symptoms are mixed 34 , whereas VEGR1/Flt-1 and VEGFR2/KDR dysregulation were associated with worse psychotic symptoms in a prospective familial high risk for psychosis study 35 , 36 , a post mortem SZ study 10 , and in case reports of systemic VEGFR1/Flt-1 administration 19 , 20 , 37 . Additionally, treatment with antipsychotic or antidepressant medications has been shown to modulate VEGF levels and is associated with improved treatment outcomes in SZ, bipolar and major depressive disorder 38 41 .…”
Section: Discussionsupporting
confidence: 85%
“…However, our findings align with animal studies, which have shown that VEGFA , VEGF receptor 1 (VEGFR1/Flt-1), and VEGF receptor 2 (VEGFR2/KDR) signaling affect working memory primarily by modulating neuroplasticity at the hippocampus or through peripheral neurotrophic effects 1 6 , 33 . Our findings are further supported by human studies, which have demonstrated that the effects of psychotic symptoms are mixed 34 , whereas VEGR1/Flt-1 and VEGFR2/KDR dysregulation were associated with worse psychotic symptoms in a prospective familial high risk for psychosis study 35 , 36 , a post mortem SZ study 10 , and in case reports of systemic VEGFR1/Flt-1 administration 19 , 20 , 37 . Additionally, treatment with antipsychotic or antidepressant medications has been shown to modulate VEGF levels and is associated with improved treatment outcomes in SZ, bipolar and major depressive disorder 38 41 .…”
Section: Discussionsupporting
confidence: 85%
“…in their plasma. 38,39 Our findings are not at variance with the results from the postmortem expression studies performed by other global down-regulation of mitochondrial genes. 42 Hakak et al (2001) discovered differential expression of myelination-related genes in schizophrenia suggesting a disruption of oligodendrocyte function 43 , a finding that has been confirmed by other expression and proteomic studies 44 .…”
Section: Discussionsupporting
confidence: 58%
“…At the central nervous system level, the precise role of sFlt-1 in modifying neuroanatomical and vascular architecture, and circulatory characteristics in the brain is unknown. Interestingly, high circulating levels of sFlt-1 are associated with adult psychiatric and neurological alterations ( Kim et al, 2007 ; Fulzele and Pillai, 2009 ; Emanuele et al, 2010 ; Lee et al, 2010 ; Lizano et al, 2016 , 2017 ; Pillai et al, 2016 ) and studies also reveal a reduction in total frontal lobe volume in patients with schizophrenia/schizoaffective disorder ( Pillai et al, 2016 ). Whether this association is the result of alterations in microvascular development in those patients is unknown, however, gene transfer of sFlt-1 in rats leads to a reduction in brain edema and in blood brain barrier permeability, suggesting a direct effect on brain endothelium ( Kumai et al, 2007 ).…”
Section: Vegf Family and Preeclampsiamentioning
confidence: 99%